Eyelid Verrucous Sporotrichosis Caused by Sporothrix Brasiliensis Mimicking Cutaneous Leishmaniasis and Complicated by Drug–Drug Interaction - Felipe Tavares Rodrigues; Amanda Ribeiro dos Santos; Sandro Rogério de Almeida; Renata Chaves Albuquerque; Regina Casz Schechtman; Sueli Carneiro (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Sporotrichosis caused by Sporothrix brasiliensis is endemic in Brazil and may present with atypical clinical features. We report a case of verrucous sporotrichosis of the eyelid mimicking cutaneous leishmaniasis in a 28-year-old woman without cat exposure or trauma. Initial diagnostic studies were inconclusive, and prolonged treatment with oral itraconazole failed. Subsequent fungal culture and polymerase chain reaction established the diagnosis. Medication review revealed concomitant pantoprazole use, likely impairing itraconazole absorption through pH-dependent bioavailability. Lesion resolution occurred after a 3-month course of oral terbinafine. This case highlights two critical considerations: sporotrichosis should remain in the differential diagnosis of chronic verrucous lesions in endemic regions, and careful evaluation of drug–drug interactions is essential to prevent antifungal treatment failure.